2015
DOI: 10.1007/s12205-015-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

Group effect of dragload in pile groups embedded in consolidating soil under embankment load

Abstract: In this paper, model tests and numerical simulations on 3 × 3 pile group embedded in consolidating soil under embankment load with different pile spacings are carried out. Single pile and 2 × 2 pile group are studied for comparative analyses. The performances of dragload versus relative displacement of pile-soil, load sequence and load rate, and the group effects of dragload and downdrag versus pile spacing are analyzed. A case study on dragload of a pile group considering with or without couple effect is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Many researchers [5]; [6]; [7] found that the piles within a group may suffer some reduction in capacity compared with single isolated piles due to interaction effects. The behavior of an individual pile within the group is different from that of a single pile, and several factors may be influenced by the behavior of group piles [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers [5]; [6]; [7] found that the piles within a group may suffer some reduction in capacity compared with single isolated piles due to interaction effects. The behavior of an individual pile within the group is different from that of a single pile, and several factors may be influenced by the behavior of group piles [8].…”
Section: Introductionmentioning
confidence: 99%
“…Abdrabbo [12] acquired the effect of pile top load and soil layer additional load through three-dimensional nonlinear analysis. Kong [13] acquired the results that when the relative displacement reaches to 2mm, the negative friction account for 75-95 percent of the maximum and the neutral surface becomed steady when the consolidation time was 240 hours through model tests and numerical analysis. Hong [14] discovered that the depth of neutral point of drilled pile equaled to 0.04-0.06H (H was the thickness of clay layer).…”
Section: Introductionmentioning
confidence: 99%